2020
DOI: 10.3390/molecules25246025
|View full text |Cite
|
Sign up to set email alerts
|

Phenolic Constituents of Lamium album L. subsp. album Flowers: Anatomical, Histochemical, and Phytochemical Study

Abstract: Flos Lamii albi has a high biological activity and is widely used in herbal medicine. The aim of the study was to characterize the secretory structures present in Lamium album subsp. album corolla and the location of phenolic compounds. Additionally, we carried out qualitative phytochemical analyses of flavonoids and phenolic acids. Light, fluorescence, and scanning electron microscopy were used to analyze the structure of the floral organs. The main classes of phenolic compounds and their localization were de… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
14
0
2

Year Published

2021
2021
2023
2023

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 17 publications
(16 citation statements)
references
References 63 publications
0
14
0
2
Order By: Relevance
“…As shown by our previous observations, short-stalked capitate trichomes with a 2-celled head in L. album flowers function non-synchronously [ 58 ]. The capitate trichomes located next to each other in L. album subsp.…”
Section: Discussionmentioning
confidence: 93%
See 4 more Smart Citations
“…As shown by our previous observations, short-stalked capitate trichomes with a 2-celled head in L. album flowers function non-synchronously [ 58 ]. The capitate trichomes located next to each other in L. album subsp.…”
Section: Discussionmentioning
confidence: 93%
“…Since we have not found such information in the literature so far, we present these data for the first time to fill the gap in the knowledge of this issue. Our previous study showed the presence of phenolic compounds: tannins, phenolic acids, and flavonoids in trichomes of this species [ 58 ]. The present study is a continuation and extension of our previous research.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations